Implementasi Pendekatan TaRL untuk Meningkatkan Hasil Belajar Peserta Didik Mata Pelajaran IPAS Kelas IV di Sekolah Dasar - Lailatul Anggraini; Ninik Srijani; Patuh Muhajir (STIKes Ibnu Sina Ajibarang, 2024)
This research is motivated by the low level of science and science learning which is a problem in educational development, especially at SDN Pilangrejo 02. This research is classroom action research (PTK). The aim of this research is to determine student learning outcomes by implementing the Teaching at the Right Level (TaRL) approach for class IV students on energy transformation material. There were a total of 14 children in the fourth grade that participated in this research project. Nine of the students were female, and five of the students were male. We gathered the data using a combination of observation, recording, and written examinations. Quantitative descriptive analysis was the analytical approach that was used. The findings of the research demonstrated that the use of the TaRL methodology has the potential to enhance the learning outcomes of students in the energy transformation content that is covered in the fourth grade SDN Pilangrejo 02. From the pre-cycle it can be proven that student learning outcomes have only reached 36%, which means 9 out of 14 students did not complete. Then in cycle 1 the percentage became 64%. where 9 students have obtained scores above the KKM. in cycle 2 it increased again to 79% with the number of students who scored above the KKM 11 out of 14 students. This shows that the TaRL approach is effective in improving student learning outcomes in energy transformation material.